Reproductive biology of the commercially important Indian squid Uroteuthis (Photololigo) duvaucelii (d’ Orbigny [in Ferussac & d’ Orbigny], 1835) off Mangalore, south-west coast of India - Naik, N. Rajendra; Shivaprakash, S. M.; Anjaneyappa, H. N.; Somasekhara, S. R.; Naik, Jaya; Benakappa, S. (Indian Journal of Fisheries, 2017)
Uroteuthis (Photololigo) duvaucelii is one of the commercially important inshore squid resources off the south-west coast of India. Length-weight relationship for this species indicated no significant difference between the sexes and hence, the relationship for both the sexes was represented with the common equation W = 0.4624 L2.1158. U. (P.) duvaucelii spawned throughout the year with peak spawning in May. Absolute fecundity ranged from 1,545 to 13,585 eggs with an average of 7,554 eggs. Size at first maturity indicated that females matured earlier at 70 mm DML (dorsal mantle length) whereas males matured little later at 90 mm DML. Males were observed to be dominant during most of the study period with overall male to female ratio of 1:0.93. Seasonal and size dependent variations in sex ratio were distinct.